Analisis Implementasi Program Ponek Di Rsud Sleman Melalui Pendekatan Model Van Meter Van Horn - Siti Ropingah Sirojudin; Cipta Pramana Pramana; Gunarmi Gunarmi (JURNAL KESEHATAN REPRODUKSI, 2022)
Background: The maternal mortality rate, newborns in Sleman Regency is quite high. The death rate can be prevented by implementing the Emergency Neonatal Care (EmNC) program. RSUD Sleman is a 24-hour EmNC hospital, has been running the program since 2012.Objectives: To find out the EmNC program at RSUD Sleman through the Van Meter Van Horn model approach to see the implementation performance on aspects: standards, targets, and policy objectives; resource; communication between units, organizational character; attitude of the implementers.Method: Research with a mix method approach. Quantitative data were collected through questionnaires, and qualitative data through in-depth interviews with key informants: the person in charge of the program, doctors, nurses, midwives, and management leaders. Data analysis using qualitative descriptive analysis techniques.Results and Discussion: Aspects of standards, goals, policy objectives of the EmNC program, resources, inter-organizational communication are included in the good category. On the aspect of organizational characteristics, and the attitude of the implementers in the sufficient category.Conclusion: The performance of the implementation of the EmNC program policy at RSUD Sleman from the aspect of standards, goals, objectives, and resources, communication between organizations is categorized as good, but the aspects of organizational characteristics and attitude of the implementers are categorized as adequate.Keywords: emergency; obstetrics; neonates; service; vanmeter van horn.